Automated building lighting control by using R3 Arduino Uno - Yolanda Putri, Annisa; Habibullah (Journal of Industrial Automation and Electrical Engineering, 2025)
Lighting is a fundamental need in daily life; however, conventional lighting systems that are still widely used today tend to be inefficient due to manual operation. This often leads to energy waste, especially when lights are left on during the day or in unoccupied rooms. This final project discusses the design and implementation of an automatic lighting system based on a light sensor (LDR) and motion sensor (PIR), aimed at improving energy efficiency in building environments. The system is designed to activate the lights only when two conditions are met simultaneously: the presence of a person in the room and low ambient light intensity, using an AND logic as the decision-making basis. Test results show that the system responds accurately, consistently, and reliably to environmental changes, and is capable of significantly reducing electricity consumption. By adopting this automation technology, the system not only supports energy savings and reduces operational costs but also contributes to environmental preservation through the reduction of carbon footprint.